Un essai de typologie à l’appui de l’utilisation des jeux par les aînés - Louise Sauvé; Lise Renaud; David Kaufman; Emmanuel Duplàa (Communiquer)
The use of digital or non-digital games as a communication medium was examined among 317 Quebec seniors over the age of 55. In order to better understand the habits of digital or non-digital games, the creation of a typology was essential to classify the survey data under discriminatory categories. We first analyzed some fifteen typologies and taxonomies on games to retain the De Kerval (2009) ranking as a starting point. Then, we classified the games used by the seniors into four categories: board games, card games, coin games and dice games. This typology, based on a detailed description of each game identified by our survey, allowed us to clarify De Kerval’s classification, adjust it and even add some subcategories offering a greater degree of discrimination for the classification of digital games or not.